What Are the Main Factors That Influence Purchasing Decisions at Bukalapak? - Aulia, Yasmin Rachma; Wijaya, Rahmad; Andharini, Sri Nastiti (University of Muhammadiyah Malang, 2024)
The era of globalization and online transactions has changed many aspects of human life, especially in terms of how people interact, work, shop, and make purchasing decisions. Therefore, this study examines the effect of E-service quality and promotion on purchasing decisions. This data was obtained through an online survey using a Google form for 105 respondents using a purposive sampling technique, di Kota Malang. The data analysis used in this study, namely linear regression analysis, shows that E-service quality has a significant positive effect on purchasing decisions, promotion has a positive and significant effect on purchasing decisions, and promotion is more dominant than e-service quality in influencing purchasing decisions. This finding implies that e-commerce, especially Bukalapak, needs to continue to improve the quality of their electronic services to meet customer expectations. However, sales promotion should remain the main focus of a marketing strategy, as it has a greater influence on driving purchasing decisions.